Commercial process for mass production of synthetic natural gas through the adiabatic reactors: operational characteristics of a 50‐kW pilot‐plant, influence of steam, and CO2. (16th August 2016) - Swain, Basudev; Kang, Suk‐Hwan; Kim, Jin‐Ho; Jung, Ki‐Jin; Yoo, Young‐Don; Kim, Kwang‐Jun; Koh, Dong‐Jun; Ryu, Jae‐Hong
Summary: In synthetic natural gas (SNG) reaction process, the water gas shift (WGS) reaction and methanation reaction take place simultaneously, and an insufficient supply of steam might deactivate the catalyst. In this study, the characteristics of the methanation reaction with a commercial catalyst and using a low [H2 ]/[CO] mole ratio in SNG synthesis are evaluated. The reaction characteristics at various possible process parameters are evaluated varying different process parameters such as the [H2 O]/[CO] mole ratio, [H2 ]/[CO] mole ratio, flow of different % CO2, and reaction temperature. Temperature profiles on catalyst bed are monitored as a function of the [H2 O]/[CO] mole ratio, [H2 ]/[CO] mole ratio, and flow of different % CO2 . Through a lab‐scale optimization process, suitable optimum conditions are selected and in the same condition a 50‐kW pilot‐scale SNG production process through adiabatic reactors is carried out. The pilot scale SNG reaction is stable through overnight and the CO conversion efficiency and CH4 selectivity are 100% and 97.3%, respectively, while the maximum CH4 productivity is 0.654 m 3 /kgcat · h. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The commercial process for mass production of synthetic natural gas (SNG) through the 50‐kW pilot‐scale adiabatic reactors has been investigated. Through the pilot‐scale SNG synthesis process 100% of the CO conversion and 96–97.3% of CH4 selectivity were achieved. The reported process addresses the gaps among lab, pilot plant, and commercial scale process. The commercial catalyst used for the SNG synthesis purpose was efficient. From the catalytic efficiency perspective, the CH4 productivity of SNG was 0.645–0.654 m 3 /kgcat · h.